IMPACT OF TECHNOLOGY ACCEPTANCE ON ADOPTION OF EHRM IN EXSO CONSULTANCY, JEDDAH - Walaa Sameer Aljahdali; Noshaba Batool (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
EHRM is a technical advancement which is used in performing various HR practices. Based on technology, EHRM made process and behaviour faster and user-friendly. Technology included information technology and communication technology had an impact on the adoption of E-HR. This study is completed based on the adoption of E-HR practices by EXSO consultancy used web-based technology which included software and technical based services. E-HR practices could influence several factors such as recruitments, selections, payrolls, performance management, benefits regarded salary or bonus or others. In this study, three general and effective methods such as semi-structured interview, questionnaire survey research and document reconsideration and analysis had been used for data collection and information. The result showed there was correlation between EHRM and faster HR practices. EXSO consultancy was worked efficiently through EHRM while HR practices became faster.